The relation of microbiologic data to aspartate aminotransferase enzyme activity in gingival crevicular fluid - YILMAZ, SEBİHA NİHAL; KADİR, TANJU (My University, 1996)
Gingival crevicular fluid (GCF), reflects the immune and inflammatory reactions and is itself a location for specific host-microbe interactions that lead to periodontal diseases. Aspartate aminotransferase (AST) is one of the components of GCF that is released as a result of cell death. In this study, 40 periodontal sites in 10 early onset periodontitis patients before and after nonsurgical periodontal therapy, with and without local metronidazole administration, were first examined for the AST enzyme levels in GCF and then evaluated for microbiological and clinical variables. In each patient, 4 sites (one site/quadrant) with a probing depth of > or = 5 mm were selected and treated with separate treatment protocols. Certain microbial species including Prevotella intermedia, Porphyromonas gingivalis, and Actinobacillus actinomycetemcomitans(A. a.) were found more often and/or in higher levels in AST active sites (36/40 first measurement--9/36 second measurement), while other species (Streptococcus and Actinomyces) were found more often and/or in higher levels in AST inactive sites (4/40 first measurement--8/36 second measurement). Eight post-treatment AST active sites revealed 1.5 mm of attachment loss, whereas 8 post-treatment AST inactive sites showed 1.37 mm of attachment gain. AST activity and microbiological-clinical data presenting such an agreement suggests that, AST level assessment would be beneficial as an adjunctive method alongside other clinical criteria, in guiding the clinician in periodontal treatment.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine